Resistivity investigation for well-site definition around Barika Village, Southeast Sulaimany city, Iraqi Kurdistan region. - Ghaib, A. F.; Abdulla, H.; Anwar, H. (Bulletin of the Geological Society of Greece, 2013)
An electrical resistivity survey involving Vertical Electrical Soundings (VES) was carried out in the Barika collective village, southeast of Sulaimany City in the Iraqi Kurdistan Region, to study groundwater characteristics such as depth, thickness and aquifer boundaries. Vertical electrical soundings by Schlumberger array were conducted in this area. The resistivity Schlumberger soundings which have a maximum current electrode spacing (AB) of 800m were carried out at fourteen sites along lines in the NE-SW and NW-SE directions. Interpretation of these soundings showed the presence of three geoelectrical horizons. The upper one is representing the alluvial deposits with 3Ωm to 60Ωm range of resistivity values reflecting the heterogeneity of the slope deposits. The middle one is taken to be the unconfined jointed aquifer represented by the Tanjero Formation with a resistivity range of 10Ωm to 42Ωm and a thickness range of 24m to 106m. The third horizon is representing the lower part of the Tanjero Formation with a relatively high resistivity range of 51Ωm to 556Ωm. Based on these results and upon our recommendations, a successful water well was drilled yielding quite enough amount of fresh water.